2003
DOI: 10.1242/dev.00898
|View full text |Cite
|
Sign up to set email alerts
|

The pro-apoptotic gene Bax is required for the death of ectopic primordial germ cells during their migration in the mouse embryo

Abstract: In the mouse embryo, significant numbers of primordial germ cells (PGCs)fail to migrate correctly to the genital ridges early in organogenesis. These usually die in ectopic locations. In humans, 50% of pediatric germ line tumors arise outside the gonads, and these are thought to arise from PGCs that fail to die in ectopic locations. We show that the pro-apoptotic gene Bax,previously shown to be required for germ cell death during later stages of their differentiation in the gonads, is also expressed during ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 28 publications
8
108
2
Order By: Relevance
“…It has long been known that the receptor tyrosine kinase Kit and its ligand stem cell factor regulate the migration, proliferation, and/or survival of PGCs (Mintz & Russell 1957, McCoshen & McCallion 1975, Buehr et al 1993, Gu et al 2009), presumably through the AKT/MTOR/BAX signaling pathway (De Miguel et al 2002, Stallock et al 2003, Runyan et al 2006. Similarly, mutations of RNA-binding proteins such as NANOS3, TIAL1, and DND1 have been known to lead to the loss of germ cells due to the failure of survival and/or proliferation of PGCs (Beck et al 1998, Tsuda et al 2003, Youngren et al 2005.…”
Section: Key Regulators For Pgc Specificationmentioning
confidence: 99%
“…It has long been known that the receptor tyrosine kinase Kit and its ligand stem cell factor regulate the migration, proliferation, and/or survival of PGCs (Mintz & Russell 1957, McCoshen & McCallion 1975, Buehr et al 1993, Gu et al 2009), presumably through the AKT/MTOR/BAX signaling pathway (De Miguel et al 2002, Stallock et al 2003, Runyan et al 2006. Similarly, mutations of RNA-binding proteins such as NANOS3, TIAL1, and DND1 have been known to lead to the loss of germ cells due to the failure of survival and/or proliferation of PGCs (Beck et al 1998, Tsuda et al 2003, Youngren et al 2005.…”
Section: Key Regulators For Pgc Specificationmentioning
confidence: 99%
“…These mislocalised germ cells can provide an undifferentiated germ cell substrate that can transform and establish extra-gonadal germ cell tumors. It has recently been shown that a key mechanism in eliminating these mis-localised germ cells is the down-regulation of SCF and the activation of intrinsic cell death that is mediated through the pro-apoptotic gene Bax (Stallock et al, 2003;Runyan et al, 2006). Finally, TGFβ1 and ACTIVIN limit PGC proliferation in various tissue culture systems (Godin and Wylie, 1991;Richards et al, 1999).…”
Section: Survival and Proliferation: Key Aspects Of Early Germ Cell Dmentioning
confidence: 99%
“…Serum-free culture mimics a growth factor withdrawal situation. A protective effect of Bax deletion on oocyte viability following growth factor withdrawal has been demonstrated (De Felici et al 1999, Stallock et al 2003, suggesting that granulosa cells are similarly less susceptible to death following growth factor withdrawal in the absence of Bax.…”
Section: Discussionmentioning
confidence: 99%